2001
DOI: 10.1190/1.1487087
|View full text |Cite
|
Sign up to set email alerts
|

Seismoelectric wave conversions in porous media: Field measurements and transfer function analysis

Abstract: We present a series of field experiments showing the transient electric fields generated by a seismic excitation of the subsurface. After removing the powerline noise by adaptive filtering, the most prominent feature of the seismoelectric recordings is the presence of electric signals very similar to conventional seismic recordings. In one instance, we identified small‐amplitude precursory electromagnetic disturbances showing a polarity reversal on either side of the shotpoint. Concentrating on the dominant se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
190
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(201 citation statements)
references
References 24 publications
10
190
1
Order By: Relevance
“…Moreover, seismograms and electrograms at the observation site correlated well with each other [10,[15][16][17]. Theoretical and observational studies indicated that there were linear relations between the electric field and seismic velocity [10] or acceleration [17], with the coefficient (transfer function) depending on the kinetic property on the site.…”
Section: Coseismic Changesmentioning
confidence: 88%
See 4 more Smart Citations
“…Moreover, seismograms and electrograms at the observation site correlated well with each other [10,[15][16][17]. Theoretical and observational studies indicated that there were linear relations between the electric field and seismic velocity [10] or acceleration [17], with the coefficient (transfer function) depending on the kinetic property on the site.…”
Section: Coseismic Changesmentioning
confidence: 88%
“…from the ordinary coseismic variation moving with the seismic wave as recorded and studied so far [9,10,12,[14][15][16][17][18][19][20][21][22][23]. This is the first report of the detection of this kind of electric variation, that is, correlation with the seismic wave starting from the beginning of fault rupture, in our long history of electric field measurement by using a borehole antenna.…”
Section: Coseismic Changesmentioning
confidence: 91%
See 3 more Smart Citations